SENSITIVITY OF ESCHERICHIA COLI BACTERIA AGAINST ANTIBIOTIC TRIMETHOPRIM-SULFAMETHOXAZOLE, KANAMYSIN, AND ENROFLOXACIN ON LAYER CHICKEN FROM CHICKEN FARM IN PENEBEL, TABANAN, BALI - Ashley; I Nengah Kerta Besung; I Gusti Ketut Suarjana (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The use of antibiotics is still the best option to treat poultry diseases among chicken farmers. This study aims to determine the sensitivity of E. coli bacteria to the antibiotics trimethoprim-sulfamethoxazole, kanamycin, and enrofloxacin in laying hens in Penebel District, Tabanan Regency, of various ages. This study used a completely randomized design (CRD) by comparing the inhibition zones formed in the germ sensitivity test of each treatment. There were three treatments, namely germ isolates from laying hens aged 1 week, 30 weeks and over 40 weeks. Each treatment used 12 samples. The results of the sensitivity test using the Kirby-Bauer method of 36 E. coli isolates showed that the sensitivity to trimethoprim-sulfamethoxazole and kanamycin at all ages was 100%, while to enrofloxacin, the sensitivity of 1 week old chickens was 100%, 30 weeks old was 50%, and aged over 40 weeks is 83% (17% intermediate). There was a significant difference between the sensitivity of E. coli to trimethoprim-sulfametazole and enrofloxacin in 1 week and 30 week old chickens, while the sensitivity to kanamycin was not significantly different. Treatment of colibacilosis in laying hens can still be given kanamycin and trimethoprim-sulfamethoxazole, the antibiotic enrofloxacin cannot be given to laying hens aged 30 weeksin Penebel District. It is necessary to carry out regular sensitivity tests as a basis for treating disease cases, followed by research on the link between resistance genes to several antibiotics.